2011
DOI: 10.1007/jhep07(2011)036
|View full text |Cite
|
Sign up to set email alerts
|

Lattice QCD without topology barriers

Abstract: As the continuum limit is approached, lattice QCD simulations tend to get trapped in the topological charge sectors of field space and may consequently give biased results in practice. We propose to bypass this problem by imposing open (Neumann) boundary conditions on the gauge field in the time direction. The topological charge can then flow in and out of the lattice, while many properties of the theory (the hadron spectrum, for example) are not affected. Extensive simulations of the SU(3) gauge theory, using… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
258
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 248 publications
(262 citation statements)
references
References 33 publications
4
258
0
Order By: Relevance
“…Such an obstruction could be overcome by the development of new MonteCarlo algorithms. Proposals in this respect have been made in the past [77,78] and some new strategies have been put forward quite recently [79,80]. In view of the exploration of higher temperatures, one should also consider the inclusion of dynamical charm quarks.…”
Section: Jhep03(2016)155mentioning
confidence: 99%
“…Such an obstruction could be overcome by the development of new MonteCarlo algorithms. Proposals in this respect have been made in the past [77,78] and some new strategies have been put forward quite recently [79,80]. In view of the exploration of higher temperatures, one should also consider the inclusion of dynamical charm quarks.…”
Section: Jhep03(2016)155mentioning
confidence: 99%
“…The infamous problem of topology freezing that affects large volume simulations [20,21], has recently been shown to also affect step scaling studies [22,23]. To overcome this problem it has been proposed [23] to use a setup with mixed boundary conditions.…”
Section: Msmentioning
confidence: 99%
“…In [6] evidence was given that when open boundary conditions are used the integrated autocorrelation time of the topological charge increases like 1/a 2 as a → 0, which is a much slower increase than expected from periodic boundary conditions. This suggested that open boundary conditions can produce a dramatic speedup of the topological charge in QCD simulations.…”
Section: Introductionmentioning
confidence: 99%
“…In order to get around this it has been proposed to switch from periodic boundary conditions to "open" boundary conditions on the gauge field for the Euclidean time direction [6]. In [6] evidence was given that when open boundary conditions are used the integrated autocorrelation time of the topological charge increases like 1/a 2 as a → 0, which is a much slower increase than expected from periodic boundary conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation